Impact of Hydrated Lime on Cracking Performance of Asphalt Mixtures with Oxidation and Cyclic Pore Pressure. Issue 1 (2016) - Zou, Jian; Roque, Reynaldo; Lopp, George; Isola, Marco; Bekoe, Michael
This research was conducted to evaluate the impact of hydrated lime (HL) on the cracking performance of asphalt mixtures for a broad range of aggregate types, including granites and limestones. A recently developed conditioning procedure, long-term oven aging (LTOA) plus cyclic pore pressure conditioning (CPPC), was employed to simulate the effects of long-term field aging on asphalt mixtures. The energy ratio (ER) approach, which took into account mixture properties that were known to be closely related to cracking and was calibrated with cores taken from field-aged pavements throughout Florida, was used to evaluate the cracking performance of untreated and lime-treated mixtures. The results show that the introduction of HL appeared to mitigate the detrimental effects of oxidative aging and moisture (LTOA plus CPPC) on the damage and fracture-related properties of granite and limestone mixtures. This effect resulted in better cracking performance of these mixtures. Further analysis based on comparison of initial construction costs of conventional pavement structures revealed that the use of HL could result in lower costs to achieve pavements with the same level of good performance. Furthermore, this research showed that the equivalent ER criterion proposed and implemented in the cost analysis could effectively assess the impact of HL modification.